Lithium metal electrode and preparation method thereof, lithium metal battery and electric device
By forming a microporous array structure on the lithium metal layer of the lithium metal battery, the problem of the formation of branch crystals in the cycle of lithium metal batteries is solved, and the effect of reducing interface polarization and internal resistance and improving cycle stability.
Patent Information
- Application Number
- CN202411539685.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-24
AI Technical Summary
Lithium metal batteries are prone to form dendrites during repeated charge and discharge cycles, resulting in an increase in interface resistance and a decrease in cycle stability.
The lithium metal layer stacked on the surface of the stream of the stream is used. Among them, the lithium metal layer is far from the surface of the stream of the streaming. The micropore has a micropore formation structure, the diameter of the micropore is 30 μm ~ 40 μm.
By increasing the surface area of the lithium metal layer, the electrochemical reaction rate on the lithium metal surface is increased, the interface polarization and internal resistance are reduced, the formation of dendrites is delayed, and the cycle stability of the lithium metal battery is improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium metal batteries, and in particular to lithium metal electrodes and preparation methods thereof, lithium metal batteries, and electrical devices. Background Art
[0002] Lithium metal battery is a rechargeable lithium battery with lithium metal electrode as the negative electrode. Lithium metal has a high theoretical specific capacity (3860mAh / g), a low electrochemical potential (-3.040V compared to the standard hydrogen electrode) and a low density, making it an ideal negative electrode material for lithium batteries.
[0003] The negative electrode of lithium metal batteries currently used is generally a two-dimensional lithium metal foil. However, during repeated charge and discharge cycles, uneven lithium deposition will lead to the formation of dendrites. Dendrites deposited on the surface of lithium metal foil will reduce the effective contact area, thereby increasing the interface resistance and reducing the cycle stability. Summary of the invention
[0004] Based on this, the present application provides a lithium metal electrode and a preparation method thereof, a lithium metal battery, and an electrical device. The lithium metal electrode provided in the present application can delay the formation of dendrites on the interface, reduce polarization at the interface, reduce internal resistance, and thus improve the cycle stability of the lithium metal battery.
[0005] In a first aspect of the present application, a lithium metal electrode is provided, comprising a current collector and a lithium metal layer stacked on at least one surface of the current collector.
[0006] The surface of the lithium metal layer on one side away from the current collector has a micropore array structure, the diameter of the micropores in the micropore array structure is 30 μm to 40 μm, and the depth of the micropores is less than the thickness of the lithium metal layer.
[0007] In one embodiment, the lithium metal layer includes lithium powder particles and a binder, wherein at least a portion of the surface of the lithium powder particles is coated with the binder.
[0008] In one embodiment, the lithium metal layer has one or more of the following characteristics:
[0009] (1) The particle size of the lithium powder particles is 10 μm to 60 μm;
[0010] (2) The mass ratio of the lithium powder particles to the binder is (6-10):1.
[0011] In one embodiment, the lithium metal layer has one or more of the following characteristics:
[0012] (1) The thickness of the lithium metal layer is 80 μm to 100 μm;
[0013] (2) The depth of the micropores is 30 μm to 40 μm;
[0014] (3) The current collector includes copper foil.
[0015] In one embodiment, the ratio of the number of micropores to the area of the surface of the lithium metal layer away from the current collector is 5 / cm 2 ~30 pieces / cm 2 .
[0016] In a second aspect of the present application, there is provided a method for preparing the lithium metal electrode according to any one of the embodiments of the first aspect of the present application, comprising the following steps:
[0017] Applying a lithium metal layer slurry on at least one surface of the current collector and drying the slurry to prepare an intermediate;
[0018] The intermediate is subjected to microneedle pressing treatment to form the micropore array structure on the surface of the lithium metal layer away from the current collector to prepare the lithium metal electrode.
[0019] In one embodiment, the steps of preparing the lithium metal layer slurry include:
[0020] The lithium metal layer slurry is prepared by mixing lithium powder particles and a binder in a solvent.
[0021] In one embodiment, the mass ratio of the lithium powder particles and the solvent is: (6-10): (18-22).
[0022] In a third aspect of the present application, a lithium metal battery is provided, comprising a positive electrode sheet, a negative electrode sheet, a separator between the positive electrode sheet and the negative electrode sheet, and an electrolyte; the negative electrode sheet is the lithium metal electrode described in any embodiment of the first aspect of the present application.
[0023] The fourth aspect of the present application provides an electrical device, comprising the lithium metal battery described in the third aspect of the present application.
[0024] The lithium metal electrode provided by the present application has at least the following beneficial effects:
[0025] The lithium metal electrode provided in the present application includes a current collector and a lithium metal layer. The lithium metal layer has a micropore array structure of a specific diameter, and the depth of the micropores in the micropore array structure is less than the thickness of the lithium metal layer, which increases the surface area of the lithium metal layer, is conducive to improving the electrochemical reaction rate on the surface of the lithium metal, reducing the polarization at the interface between the lithium metal electrode and the electrolyte, and reducing the internal resistance. In addition, due to the presence of the micropore array structure, the lithium dendrites during the charge and discharge cycle will preferentially deposit in the micropores rather than on the surface of the exposed lithium metal layer, which delays the formation of dendrites on the interface between the lithium metal electrode and the electrolyte, thereby ensuring the transmission of lithium ions, reducing the risk of short circuits, and maintaining a stable internal structure of the battery during the charge and discharge process to improve the battery cycle efficiency.
[0026] In summary, the lithium metal battery provided in the present application can effectively increase the surface area of the metal layer to improve the electrochemical reaction rate on the lithium metal surface, and can delay the formation of dendrites on the interface between the lithium metal electrode and the electrolyte, so that it has lower internal resistance and excellent cycle performance. DETAILED DESCRIPTION
[0027] The following is a further complete and clear description of the lithium metal electrode and its preparation method, lithium metal battery, and electrical device of the present application in conjunction with specific embodiments. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0028] In the present application, the terms “further”, “furthermore”, “particularly”, etc. are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.
[0029] In this application, "optionally", "optional" and "optional" refer to optional, that is, to any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.
[0030] In the present application, when it comes to numerical intervals (i.e., numerical ranges), unless otherwise specified, the optional numerical distribution is considered continuous within the above numerical interval, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical range, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers within the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints. In this article, it is equivalent to directly listing each integer, such as t is an integer selected from 1 to 10, indicating that t is any integer selected from the group of integers consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all subranges included therein.
[0031] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.
[0032] Conventional lithium metal electrodes are generally two-dimensional lithium metal foils. Conventional lithium metal electrodes have the following disadvantages: (1) Lithium metal electrodes are prone to produce lithium dendrites during the charge and discharge cycle. Sharp lithium dendrites will continue to grow during repeated charge and discharge, and can pierce the diaphragm, causing battery short circuits or even explosions, posing a safety hazard. (2) The deposition and dissolution of lithium will cause a huge change in the volume of the negative electrode, thereby affecting the interfacial stability of the battery. Due to the unstable interface, dendrite-free and dense lithium deposition cannot be achieved, and the interfacial resistance cannot be reduced after cycling, which will affect the cycle performance of the battery.
[0033] In order to prevent the growth of lithium dendrites and the decomposition of the electrolyte, some researchers have added a passivation layer between the lithium metal electrode and the electrolyte to try to change the morphology of the lithium deposits. However, the presence of the passivation layer hinders the transmission of lithium ions between the electrode and the electrolyte, which will increase the internal resistance of the battery and reduce the charge and discharge efficiency. There is also a related technical solution of adding more inert solvents to the electrolyte. Although more inert solvents can reduce side reactions with metallic lithium, they may not perform well in dissolving electrolyte salts. This may lead to reduced ionic conductivity of the electrolyte and affect the charge and discharge performance of the battery.
[0034] Based on this, in a first aspect of the present application, a lithium metal electrode is provided, comprising a current collector and a lithium metal layer stacked on at least one surface of the current collector.
[0035] The surface of the lithium metal layer on one side away from the current collector has a micropore array structure, the diameter of the micropores in the micropore array structure is 30 μm to 40 μm, and the depth of the micropores is less than the thickness of the lithium metal layer.
[0036] It is understandable that the micropore diameter can be selected from any value between 30 μm and 40 μm. Further, the micropore diameter includes but is not limited to 30 μm, 32 μm, 33 μm, 35 μm, 36 μm, 38 μm, 39 μm, or 40 μm, or a range consisting of any of the above point values as end values.
[0037] Since lithium is relatively active, it is exposed to air and moisture, which causes the surface of lithium to be covered with a natural oxide layer. Therefore, it can be understood that the surface of the lithium metal layer of the present application also includes an oxygen-containing lithium compound. For example, the oxygen-containing lithium compound includes one or more of Li2O, Li2CO3 and LiOH.
[0038] The lithium metal electrode provided in the present application includes a current collector and a lithium metal layer. The lithium metal layer has a micropore array structure of a specific diameter, and the micropore depth of the micropore array structure is less than the thickness of the lithium metal layer, which increases the surface area of the lithium metal layer, is conducive to improving the electrochemical reaction rate on the surface of the lithium metal, reducing the polarization at the interface between the lithium metal electrode and the electrolyte, and reducing the internal resistance. In addition, due to the presence of the micropore array structure, the lithium dendrites during the charge and discharge cycle will preferentially deposit in the micropores rather than on the surface of the exposed lithium metal layer, which delays the formation of dendrites on the interface between the lithium metal electrode and the electrolyte, thereby ensuring the transmission of lithium ions, reducing the risk of short circuits, and maintaining a stable internal structure of the battery during the charge and discharge process to improve the battery cycle efficiency.
[0039] In summary, the lithium metal battery provided in the present application can effectively increase the surface area of the metal layer to improve the electrochemical reaction rate on the lithium metal surface, and can delay the formation of dendrites on the interface between the lithium metal electrode and the electrolyte, so that it has lower internal resistance and excellent cycle performance.
[0040] In one example, the microwell array structure includes a plurality of microwells.
[0041] In the present application, "micropore array structure" refers to a structure formed by arranging a plurality of micropores according to a certain rule. For example, the diameters of the plurality of micropores included in the micropore array structure are the same. Or one or more of the spacings between the micropores included in the micropore array structure are the same.
[0042] Since the surface of lithium is covered with natural oxide layers including one or more of Li2O, Li2CO3 and LiOH, these natural oxide layers will become additional resistance to lithium ion transfer during the charge and discharge process. The microporous array can further increase the specific surface area of the lithium metal layer and can remove part of the natural oxide layer, so that the microporous array has a lower charge transfer internal resistance. Furthermore, the lithium deposition rate on the microporous array is faster than the lithium deposition rate on the exposed lithium surface. Therefore, the microporous array structure can effectively reduce the actual current density and reduce the formation and growth of dendrites.
[0043] In one example, the lithium metal layer includes lithium powder particles and a binder, wherein at least a portion of the surface of the lithium powder particles is coated with the binder.
[0044] As mentioned above, in the lithium metal electrode of the present application, lithium ions are first concentratedly deposited in the microporous array structure to form dendrites.
[0045] In addition, although both lithium powder particles and lithium foil have high reactivity with electrolytes or impurities such as water and oxygen. However, the present application uses lithium powder particles, which have a higher surface area, so the surface area of lithium in contact with the electrolyte is also higher. At this time, the reaction rate of the lithium metal layer composed of lithium powder particles with impurities or electrolytes is faster than that of lithium foil. Therefore, at high charge and discharge rates, a lithium metal layer of lithium powder particles is selected, and the deposition / dissolution rate of lithium and the reaction rate ratio between lithium and impurities (or electrolyte) are lower than those of lithium foil, which can reduce the polarization at the interface between the lithium electrode and the electrolyte, reduce internal resistance, and reduce dendrites to a certain extent.
[0046] In one example, the particle size of the lithium powder particles is 10μm~60μm. It is understandable that the particle size of the lithium powder particles can be selected from any value between 10μm~60μm. Further, the particle size of the lithium powder particles includes but is not limited to 10μm, 12μm, 14μm, 15μm, 16μm, 18μm, 20μm, 22μm, 25μm, 28μm, 30μm, 32μm, 35μm, 38μm, 40μm, 42μm, 45μm, 48μm, 50μm, 52μm, 55μm, 58μm, or 60μm, or any two of the above point values as end values.
[0047] Based on rich experience and a large number of experiments, the inventors of the present application have found that the particle size of the above-mentioned lithium powder particles and the micropore diameter cooperate with each other, so that the lithium metal electrode of the present application can not only increase the specific surface area of the lithium metal layer, but also avoid the micropore diameter being too high, which will destroy the microstructure of the lithium powder particles.
[0048] In one example, the mass ratio of the lithium powder particles to the binder is (6~10):1.
[0049] It can be understood that the mass ratio of the lithium powder particles to the binder can be selected from any value between (6-10): 1. Further, the mass ratio of the lithium powder particles to the binder includes but is not limited to 6: 1, 6.5: 1, 7: 1, 7.5: 1, 8: 1, 8.5: 1, 9: 1, 9.5: 1, or 10: 1, or a range consisting of any two of the above point values as end values.
[0050] The mass ratio of lithium powder particles and binder is limited. At this time, the higher content of lithium powder particles makes the content of active substances in the electrode relatively high. As an active substance, lithium powder can provide more lithium ions to participate in the reaction during the charge and discharge process, so that the battery has a higher capacity. The binder with the above mass ratio can ensure good bonding between lithium powder particles and between the lithium metal layer and the current collector to maintain the stability of the electrode structure during the cycle. This can reduce the capacity decay caused by the destruction of the electrode structure and improve the cycle life of the battery.
[0051] In one example, the thickness of the lithium metal layer is 80 μm to 100 μm. It is understandable that the thickness of the lithium metal layer can be selected from any value between 80 μm and 100 μm. Further, the thickness of the lithium metal layer includes but is not limited to 80 μm, 83 μm, 85 μm, 88 μm, 90 μm, 93 μm, 95 μm, 98 μm, or 100 μm, or any two of the above point values as end values.
[0052] In one example, the depth of the micropores is 30 μm to 40 μm. It is understandable that the micropore depths included in the micropore array structure include but are not limited to 30 μm, 33 μm, 35 μm, 38 μm, or 40 μm, or a range formed by any two of the above point values as end values.
[0053] The thickness of the lithium metal layer and the micropore depth cooperate with each other, so that the micropore depth can not only ensure the preferential deposition of lithium dendrites, but also prevent the high micropore depth from damaging the mechanical strength of the lithium metal electrode.
[0054] In one example, the current collector includes copper foil.
[0055] In one example, the thickness of the current collector is 7 μm to 15 μm. Further, the thickness of the current collector includes but is not limited to 7 μm, 8 μm, 9 μm, 10 μm, 12 μm, 14 μm, or 15 μm, or a range formed by any two of the above points as end values.
[0056] In one example, lithium metal layers are stacked on two opposite surfaces of the current collector.
[0057] In one example, the ratio of the number of micropores to the area of the surface of the lithium metal layer away from the current collector is 5 / cm 2 ~30 pieces / cm 2 It can be understood that the ratio of the number of micropores to the area of the surface of the lithium metal layer away from the current collector can be selected from 5 / cm 2 ~30 pieces / cm 2 Further, the ratio of the number of micropores to the area of the surface of the lithium metal layer away from the current collector includes but is not limited to 5 / cm 2 , 7 pieces / cm 2 , 9 pieces / cm 2 , 11 pieces / cm 2 , 13 pieces / cm 2 , 15 pieces / cm 2 , 17 pieces / cm 2 , 20 pieces / cm 2 , 25 pieces / cm 2 , or 30 pieces / cm 2 , or the range formed by any two of the above point values as end values.
[0058] During the charging and discharging process, lithium ions need to migrate back and forth between the electrodes. Limiting the number of micropores per unit area helps provide more transmission channels for lithium ions and reduce ion transmission resistance.
[0059] Furthermore, it can increase the reaction surface area of the lithium metal electrode and effectively reduce the actual current density, thereby reducing the polarization at the interface between the lithium electrode and the electrolyte, reducing the internal resistance, and alleviating the formation and growth of dendrites. The battery made with this electrode has low charge transfer resistance and diffusion resistance, and can significantly improve the cycle life of the battery at high rates.
[0060] In a second aspect of the present application, there is provided a method for preparing the lithium metal electrode as described in any example of the first aspect of the present application, comprising the following steps:
[0061] S10, coating the lithium metal layer slurry on at least one surface of the current collector, and drying to prepare an intermediate;
[0062] S20, subjecting the intermediate to a microneedle pressing process to form a micropore array structure on the surface of the lithium metal layer away from the current collector, thereby preparing the lithium metal electrode.
[0063] In one example, in step S10, the lithium metal layer slurry is coated on two surfaces of the current collector that are opposite to each other. For example, when the lithium metal layer slurry is coated on two surfaces of the current collector that are opposite to each other, the double-sided surface density of the lithium metal layer slurry is 70 g / m 2 ~100 g / m 2 The double-sided surface density of the lithium metal layer slurry includes but is not limited to 70 g / m 2 , 75g / m 2 , 78g / m 2 , 80g / m 2 , 82g / m 2 , 83g / m 2 , 85g / m 2 , 88g / m 2 , 90g / m 2 , 95 g / m 2 , 98 g / m 2 , or 100g / m 2 , or the range formed by any two of the above point values as end values.
[0064] In one example, in step S10, after the drying step, a compaction step is further included. For example, the compaction density of the compacted lithium metal layer is 0.4 g / cm 3 ~0.6 g / cm 3 The compacted density of the lithium metal layer after compaction includes but is not limited to 0.4 g / cm 3 , 0.45 g / cm 3 , 0.5 g / cm 3 , 0.51 g / cm 3 , 0.52 g / cm 3 , 0.53 g / cm 3 , 0.54 g / cm 3 , 0.55 g / cm 3 , 0.56 g / cm 3 , 0.57 g / cm 3 , 0.58 g / cm 3 , 0.59 g / cm 3 or 0.6 g / cm 3 , or the range formed by any two of the above point values as end values.
[0065] In one example, the steps of preparing the lithium metal layer slurry include:
[0066] a1. Mixing lithium powder particles and a binder in a solvent to prepare the lithium metal layer slurry.
[0067] In one example, in step a1, the mass ratio of the lithium powder particles and the solvent is: (6-10): (18-22). It can be understood that the mass ratio of the lithium powder particles and the solvent can be selected from any value between (6-10): (18-22). Further, the mass ratio of the lithium powder particles and the solvent includes but is not limited to 6:18, 7:19, 8:20, 9:21, or 10:22, or a range formed by any two of the above point values as end values.
[0068] In one example, in step a1, the solvent includes one or more of N-methylpyrrolidone and tetrahydrofuran.
[0069] In one example, the steps of preparing the lithium powder particles include:
[0070] Under the condition of 230℃~300℃, metallic lithium is dispersed in oil medium to form a dispersion of molten lithium;
[0071] The molten lithium dispersion is cooled to prepare the lithium powder particles.
[0072] In one example, the apparatus for forming the dispersion of molten lithium is a homogenizer.
[0073] In one example, the process parameters for forming a dispersion of molten lithium include a rotation speed of 20,000 r / min to 30,000 r / min.
[0074] In one example, the method further includes filtering, washing and drying the lithium powder particles. For example, the washing solvent includes but is not limited to cyclohexane.
[0075] In a third aspect of the present application, a lithium metal battery is provided, comprising a positive electrode sheet, a negative electrode sheet, a separator separated between the positive electrode sheet and the negative electrode sheet, and an electrolyte; the negative electrode sheet is the lithium metal electrode described in any example of the first aspect of the present application.
[0076] For example, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material, a positive electrode binder and a positive electrode conductor.
[0077] Wherein, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0078] For example, the positive electrode active material is not limited to lithium iron phosphate (LiFePO4), lithium manganese phosphate (LiMnPO4), lithium cobalt phosphate (LiCoPO4), iron pyrophosphate (Li2FeP2O7), lithium cobalt oxide (LiCoO2), spinel lithium manganese oxide (LiMn2O4), spinel nickel lithium manganese oxide (LiNi 0.5 Mn 1.5 O4), layered lithium manganese oxide (LiMnO2), lithium nickel oxide (LiNiO2), lithium niobate (LiNbO2), lithium ferrite (LiFeO2), lithium magnesium oxide (LiMgO2), lithium calcium oxide (LiCaO2), lithium copper oxide (LiCuO2), lithium zinc oxide (LiZnO2), lithium molybdenum oxide (LiMoO2) and lithium tantalate (LiTaO2).
[0079] For example, the positive electrode binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0080] For example, the positive electrode conductive agent includes one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0081] The electrolyte can be in liquid, gel or solid state.
[0082] In one example, the electrolyte is an electrolyte solution, which includes a lithium salt, a solvent, and an additive.
[0083] In one example, the lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0084] In one example, the solvent includes one or more of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0085] The additive includes one or more of polyethylene oxide, acrylate polymer, pentaerythritol tetraacrylate, polyurethane and polyacrylonitrile.
[0086] The material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0087] The fourth aspect of the present application provides an electrical device, comprising the lithium metal battery described in the third aspect of the present application.
[0088] The following further specific examples are provided to explain the present application in detail. It should also be understood that the following examples are only used to further explain the present application and cannot be understood as limiting the scope of protection of the present application. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present application belong to the scope of protection of the present application. The specific process parameters of the following embodiments are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not necessarily limited to the specific values of the embodiments below.
[0089] [raw material]
[0090] Lithium powder particles: Under the condition of 245°C, metallic lithium is dispersed in hot silicone oil, and a molten lithium dispersion is formed by a homogenizer at a speed of 25,000 rpm; the molten lithium dispersion is cooled at normal pressure to prepare lithium powder particles. The lithium powder particles are filtered, and the filtered powder is washed with cyclohexane, then dried at room temperature for 5 hours, and sieved with screens of different particle sizes to prepare lithium powder particles.
[0091] Example 1
[0092] Lithium powder particles (particle size 15 μm), a binder PVDF, and a solvent tetrahydrofuran were mixed in a mass ratio of 8:1:20 to prepare a lithium metal layer slurry.
[0093] The lithium metal layer slurry is coated on a 9μm thick copper foil, and the double-sided surface density after coating is 85g / m 2The coated electrode was dried at 85°C and then rolled by a roller. The compaction density after rolling was 0.52g / cm 3 The thickness of the lithium metal layer on one side after rolling is 82μm. The electrode after rolling is treated with a microneedle rubber roller to form an array of micropores with an average depth of 40μm and an average surface pore size of 40μm on the surface of the electrode. The ratio of the number of micropores included in the micropore array structure to the area of the surface of the lithium metal layer away from the current collector is 5.4 / cm 2 .
[0094] Example 2
[0095] Lithium powder particles (particle size 15 μm), a binder PVDF, and a solvent tetrahydrofuran were mixed in a mass ratio of 8:1:20 to prepare a lithium metal layer slurry.
[0096] The lithium metal layer slurry is coated on a 9μm thick copper foil, and the double-sided surface density after coating is 85g / m 2 The coated electrode was dried at 85°C and then rolled by a roller. The compaction density after rolling was 0.52g / cm 3 The thickness of the lithium metal layer on one side after rolling is 82μm. The rolled electrode is treated with a microneedle rubber roller to form an array of micropores with an average depth of 30μm and an average surface pore size of 30μm on the surface of the electrode. The ratio of the number of micropores included in the micropore array structure to the area of the surface of the lithium metal layer away from the current collector is 10.7 / cm 2 .
[0097] Example 3
[0098] Lithium powder particles (particle size 35 μm), a binder PVDF, and a solvent tetrahydrofuran were mixed in a mass ratio of 8:1:20 to prepare a lithium metal layer slurry.
[0099] The lithium metal layer slurry was coated on a 9μm thick copper foil. The double-sided surface density after coating was 89g / m 2 The coated electrode was dried at 85°C and then rolled by a roller. The compaction density after rolling was 0.5g / cm 3 The thickness of the lithium metal layer on one side after rolling is 88μm. The rolled electrode is treated with a microneedle rubber roller to form an array of micropores with an average depth of 30μm and an average surface pore size of 30μm on the surface of the electrode. The ratio of the number of micropores included in the micropore array structure to the area of the surface of the lithium metal layer away from the current collector is 10.7 / cm 2 .
[0100] Example 4
[0101] Lithium powder particles (particle size 45 μm), a binder PVDF, and a solvent tetrahydrofuran were mixed in a mass ratio of 8:1:20 to prepare a lithium metal layer slurry.
[0102] The lithium metal layer slurry was coated on a 9μm thick copper foil, and the double-sided surface density after coating was 88g / m 2 The coated electrode was dried at 85°C and then rolled by a roller. The compaction density after rolling was 0.48 g / cm 3 The thickness of the lithium metal layer on one side after rolling is 91μm. The electrode after rolling is treated with a microneedle rubber roller to form an array of micropores with an average depth of 40μm and an average surface pore size of 40μm on the surface of the electrode. The ratio of the number of micropores included in the micropore array structure to the area of the surface of the lithium metal layer away from the current collector is 5.4 / cm 2 .
[0103] Example 5
[0104] Lithium powder particles (particle size 60 μm), a binder PVDF, and a solvent tetrahydrofuran were mixed in a mass ratio of 8:1:20 to prepare a lithium metal layer slurry.
[0105] The lithium metal layer slurry was coated on a 9μm thick copper foil. The double-sided surface density after coating was 91g / m 2 The coated electrode was dried at 85°C and then rolled by a roller. The compaction density after rolling was 0.47 mg / cm 2 The thickness of the lithium metal layer on one side after rolling is 96μm. The rolled electrode is treated with a microneedle rubber roller to form an array of micropores with an average depth of 40μm and an average surface pore size of 40μm on the surface of the electrode. The ratio of the number of micropores included in the micropore array structure to the area of the surface of the lithium metal layer away from the current collector is 5.4 / cm 2 .
[0106] Example 6
[0107] Lithium powder particles (particle size 15 μm), a binder PVDF, and a solvent tetrahydrofuran were mixed in a mass ratio of 8:1:20 to prepare a lithium metal layer slurry.
[0108] The lithium metal layer slurry is coated on a 9μm thick copper foil, and the double-sided surface density after coating is 85g / m 2 The coated electrode was dried at 85°C and then rolled by a roller. The compaction density after rolling was 0.52g / cm 3The thickness of the lithium metal layer on one side after rolling is 82μm. The rolled electrode is treated with a microneedle rubber roller to form an array of micropores with an average depth of 40μm and an average surface pore size of 40μm on the surface of the electrode. The ratio of the number of micropores included in the micropore array structure to the area of the surface of the lithium metal layer away from the current collector is 26.8 / cm 2 .
[0109] Comparative Example 1
[0110] In Comparative Example 1, a 100 μm thick lithium metal foil was selected as the lithium metal electrode.
[0111] Comparative Example 2
[0112] Lithium powder particles (particle size 15 μm), a binder PVDF, and a solvent tetrahydrofuran were mixed in a mass ratio of 8:1:20 to prepare a lithium metal layer slurry.
[0113] The lithium metal layer slurry was coated on a 9μm thick copper foil, and the double-sided surface density after coating was 44g / m 2 The coated electrode was dried at 85°C and then rolled by a roller. The compaction density after rolling was 0.53g / cm 3 The thickness of the lithium metal layer on one side after rolling is 40μm. The rolled electrode is treated with a microneedle rubber roller to form an array of micropores with an average depth of 40μm and an average surface pore size of 40μm on the surface of the electrode. The ratio of the number of micropores included in the micropore array structure to the area of the surface of the lithium metal layer away from the current collector is 5.4 / cm 2 .
[0114] Comparative Example 3
[0115] Lithium powder particles (particle size 15 μm), a binder PVDF, and a solvent tetrahydrofuran were mixed in a mass ratio of 8:1:20 to prepare a lithium metal layer slurry.
[0116] The lithium metal layer slurry was coated on a 9μm thick copper foil, and the double-sided surface density after coating was 32g / m 2 The coated electrode was dried at 85°C and then rolled by a roller. The compaction density after rolling was 0.53g / cm 3 The thickness of the lithium metal layer on one side after rolling is 30μm. The rolled electrode is treated with a microneedle rubber roller to form an array of micropores with an average depth of 30μm and an average surface pore size of 30μm on the surface of the electrode. The ratio of the number of micropores included in the micropore array structure to the area of the surface of the lithium metal layer away from the current collector is 5.4 / cm 2 .
[0117] Test Case
[0118] The lithium metal electrode prepared in the embodiment and the comparative example was used as the negative electrode, and a lithium polymer battery was prepared by a method of stacking the negative electrode, the positive electrode and the polymer electrolyte.
[0119] Among them, the preparation steps of the positive electrode include: mixing and grinding the active material LiCoO2 (LCO) with the conductive agent Super P and the binder PVDF in a mass ratio of 10:1.5:1.5 respectively, adding N-methylpyrrolidone to make a positive electrode slurry, coating the positive electrode slurry on aluminum foil, and rolling the positive electrode slurry after drying.
[0120] The preparation steps of lithium polymer batteries include:
[0121] Weigh pentaerythritol tetraacrylate and lithium salt LiTFSI in a mass ratio of 8:2, mix thoroughly, add ethylene carbonate and ethyl butyrate (7:3, v / v) solvent and 0.1wt% azobisisobutyronitrile to obtain a precursor liquid. Inject the precursor liquid into the glass fiber separator, react at 60°C for 10h to initiate in-situ polymerization, and prepare a polymer electrolyte gel membrane. Then place positive and negative electrode sheets on both sides of the polymer electrolyte gel membrane, respectively, and encapsulate it in an aluminum-plastic film to prepare a lithium polymer battery.
[0122] The battery was charged, discharged and cycled: charged at a constant current for a given time with an upper potential limit of 4.2 V, and then discharged at a constant current with a cut-off voltage of 3.0 V.
[0123] Impedance tests (charge transfer resistance, diffusion resistance) were measured using an impedance analyzer. The frequency range and amplitude were set to 50 m ~ 1 MHz and 5 mV, respectively. All electrical measurements were performed at open circuit voltage. The corresponding test results are shown in Table 1.
[0124] Table 1
[0125]
[0126] In Comparative Example 1, only lithium metal foil is selected as the lithium metal electrode. At this time, polarization is severe, and the formation of lithium dendrites cannot be effectively delayed, resulting in increased internal resistance and reduced capacity retention. In Comparative Examples 2 and 3, the depth of the micropores included in the micropore array structure is consistent with the thickness of the lithium metal layer. At this time, the pole piece is thinner and the internal resistance decreases. At the same time, the copper foil is easily exposed or damaged, resulting in severe powder loss of the pole piece dendrites during charging and discharging, causing the lithium polymer battery to short-circuit, and thus the capacity retention rate of 100 cycles at a 5C rate was not tested.
[0127] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0128] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the content of the attached claims, and the description can be used to interpret the content of the claims.
Claims
1. A lithium metal electrode, characterized in that comprising a current collector and a lithium metal layer stacked on at least one surface of the current collector, The surface of the lithium metal layer on one side away from the current collector has a micropore array structure, the diameter of the micropores in the micropore array structure is 30 μm to 40 μm, and the depth of the micropores is less than the thickness of the lithium metal layer.
2. The lithium metal electrode according to claim 1, characterized in that The lithium metal layer includes lithium powder particles and a binder, wherein at least a portion of the surfaces of the lithium powder particles are coated with the binder.
3. The lithium metal electrode according to claim 2, characterized in that The lithium metal layer has one or more of the following characteristics: (1) The particle size of the lithium powder particles is 10 μm to 60 μm; (2) The mass ratio of the lithium powder particles to the binder is (6-10):
1.
4. The lithium metal electrode according to any one of claims 1 to 3, characterized in that The lithium metal layer has one or more of the following characteristics: (1) The thickness of the lithium metal layer is 80 μm to 100 μm; (2) The depth of the micropores is 30 μm to 40 μm; (3) The current collector includes copper foil.
5. The lithium metal electrode according to any one of claims 1 to 3, characterized in that The ratio of the number of the micropores to the area of the surface of the lithium metal layer away from the current collector is 5 / cm 2 ~30 pieces / cm 2 .
6. A method for preparing the lithium metal electrode according to any one of claims 1 to 5, characterized in that: The following steps are involved: Applying a lithium metal layer slurry on at least one surface of the current collector and drying the slurry to prepare an intermediate; The intermediate is subjected to microneedle pressing treatment to form the micropore array structure on the surface of the lithium metal layer away from the current collector to prepare the lithium metal electrode.
7. The method for preparing a lithium metal electrode according to claim 6, characterized in that: The steps of preparing the lithium metal layer slurry include: The lithium metal layer slurry is prepared by mixing lithium powder particles and a binder in a solvent.
8. The method for preparing a lithium metal electrode according to claim 7, characterized in that: in, The mass ratio of the lithium powder particles and the solvent is: (6-10): (18-22).
9. A lithium metal battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, a separator between the positive electrode sheet and the negative electrode sheet, and an electrolyte; the negative electrode sheet is the lithium metal electrode according to any one of claims 1 to 6.
10. An electrical device, characterized in that: Including the lithium metal battery as described in claim 9.